Hubungan Penggunaan Media Pembelajaran Terhadap Minat Belajar Siswa Kristen SMP Negeri 41 Medan - Zebua, Afolo; Silaban, Petrus Posma (Sekolah Tinggi Teologi Baptis Medan, 2023)
AbstractLearning media is one of the factors that has a significant effect on facilitating the learning process and helping students understand and absorb the subject matter more effectively. The use of multimedia in the digital era, especially in the learning process, is inseparable from the use of technology so that students can increase their interest in learning. The purpose of this study was to determine the use of media-based learning media, the level of student interest in learning, and the relationship of multimedia-based learning media to student learning requests. The method used is research with a quantitative approach, using the ex post facto model, learning media, the role of media in learning, the use of learning media, the effect of using media in learning, the benefits obtained through the presentation of learning using media, human-based media, multimedia, visual-based media, principles of visual utilization, audio-visual media, interest, learning, and factors that affect learning interest. The results found indicate that the use of multimedia-based media is low, with lower and upper bound values located in the medium-to-high category. Student Learning Interest is found to be moderate to high Lower Bound and Upper Bound are in the moderate interval class. then, there is a significant relationship between the Use of Multimedia-Based Learning Media and Student Learning Interest There is a significant relationship between the use of multimedia-based learning media and student learning interest, with a ryx value of 42.5% and a positive value. So it is concluded that the first hypothesis, which says low, is not proven, the second hypothesis, which says low, is not proven, and the third hypothesis, that there is a significant relationship between the two variables. Keywords: learning media, learning interest, Christian students AbstrakMedia pembelajaran menjadi salah satu faktor yang berpengaruh signifikan dalam memfasilitasi proses pembelajaran, membantu siswa dalam memahami dan meresapkan materi pelajaran dengan lebih efektif. Penggunaan multimedia di era digital terutama dalam proses pembelajaran, tidak terlepas dari pemanfaatan teknologi agar siswa dapat meningkatkan minat belajarnya. tujuan penelitian ini adalah untuk mengetahui pengguaan media pembelajaran berbasis media, tingkat minat belajar siswa, serta hubungan media pembelajaran berbasis multimedia terhadap minta belajar mahasiswa. Adapun metode yan digunakan adalah penelitian dengan mendekatan kuantitatif, dengan menggunakan model ex post facto, media pembelajaran, peran media dalam pembelajaran, pemanfaatan media pembelajaran, pengaruh penggunaan media dalam pembelajaran, manfaat yang diperoleh melalui penyajian pembelajaran dengan menggunakan media, media berbasih manusia, multimedia, media berbasis visual, prinsip-primnsip pemanfaatan visual, media audia-visual, minat, belajar, faktor-faktor yang mempengaruhi minat belajar. Hasil yang ditemukan yaitu penggunaan media berbasis multimedia adalah rendah dengan nilai lower bound dan upper bound terletak pada kategori sedang menuju tinggi. Minat Belajar Siswa ditemukan adalah sedang menuju tinggi Lower Bound dan Upper Bound ada pada klas interval sedang. kemudian, terdapat hubungan yang signifikan antara Penggunaan Media Pembelajaran Berbasis Multimedia Terhadap Minat Belajar Siswa Terdapat hubungan yang signifikan antara Penggunaan Media Pembelajaran Berbasis Multimedia Terhadap Minat Belajar Siswa dengan nilai ryx sebesar 42,5% dan bernilai positif. Maka disimpulkan bahwa hipotesis pertama yang mengatakan rendah tidak terbukti, hipotesis kedua yang mengatakan rendah tidak terbukti, dan hipotesis ketiga terdapat hubungan yang signifikan antara kedua variabel. Kata Kunci: media pembelajaran, minat belajar, siswa kristen